Sostenibilidad y desarrollo en una sociedad multicultural: Sustainability and Development in a Multicultural Society - Crespo, Julio E.; Dutra e Silva, Sandro; Caldevilla Domínguez, David (Universidad del Zulia, 2022)
The research aims to analyze sustainability as an opportunity to overcome the crises generated by the rapacity of contemporary society. Measure is promoted, responsibility towards other forms of life, as assets capable of shaping modes of production that, when considering the limits of reality, guarantee survival. Meanwhile, humanization requires considering the formation of multicultural societies. It deals with the fact that it is impossible to articulate coherent production without establishing livable societies by considering the human plural condition. It is a diachronic bibliographic study from the rationalist-deductive approach.